2010
DOI: 10.1371/journal.pone.0011033
|View full text |Cite
|
Sign up to set email alerts
|

Switch from Stress Response to Homeobox Transcription Factors in Adipose Tissue After Profound Fat Loss

Abstract: BackgroundIn obesity, impaired adipose tissue function may promote secondary disease through ectopic lipid accumulation and excess release of adipokines, resulting in systemic low-grade inflammation, insulin resistance and organ dysfunction. However, several of the genes regulating adipose tissue function in obesity are yet to be identified.Methodology/Principal FindingsIn order to identify novel candidate genes that may regulate adipose tissue function, we analyzed global gene expression in abdominal subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 54 publications
12
99
0
1
Order By: Relevance
“…6). Prrx1 expression also increases in subcutaneous WAT after fat loss during bariatric surgery (62). Together, these data suggest that altered metabolic states impact WAT Prrx1 expression in both mice and humans.…”
Section: Discussionmentioning
confidence: 71%
“…6). Prrx1 expression also increases in subcutaneous WAT after fat loss during bariatric surgery (62). Together, these data suggest that altered metabolic states impact WAT Prrx1 expression in both mice and humans.…”
Section: Discussionmentioning
confidence: 71%
“…Extracellular matrix remodelling plays a crucial role in adipose tissue expandability. 33 Collagen protein COL1A1 is a major ECM gene in adipose tissue which expression level is increased after weight loss 34 or reduced in obese adipose tissue. 35 Collagen COL3A1 expression is higher after weight loss 34 and its turnover is regulated by the metalloprotease MMP9 in human adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…33 Collagen protein COL1A1 is a major ECM gene in adipose tissue which expression level is increased after weight loss 34 or reduced in obese adipose tissue. 35 Collagen COL3A1 expression is higher after weight loss 34 and its turnover is regulated by the metalloprotease MMP9 in human adipose tissue. 35 MMP9 itself is involved in ECM remodeling, with increased expression during adipogenesis, 36 its expression is reduced after weight loss 37 and increased in obese stroma-vascular fraction 38 and in adipose tissue with obesity-associated insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…found that the profound fat loss via bariatric surgery significantly upregulated the HOX gene expression in the abdominal subcutaneous adipose from the obese patient. 29 The mechanistic understanding of how the HOX network controls adipogenesis needs to be investigated in depth.…”
Section: 18mentioning
confidence: 99%